THE NATURE, OBJECTIVITY AND EXPRESSION OF MYSTICAL EXPERIENCE: With a Special Reference to Walter T. Stace and Steven T. Katz - Fatma Yüce (Felsefe Dünyası)
Both Walter T. Stace and Steven T. Katz play an important role as regards the mysticalexperience with their opposite arguments concerning the ‘universal core’. Therefore inthis article the nature, objectivity and expression of mystical experience is discussed throughtheir arguments. It is seen that their understanding of mystical experience is quitedifferent; so is their inference for the problem of objectivity. They only have a commonconsideration as to the issue of expression. Stace defines mystical experience beyond cultureand irrelevant to religion, whereas Katz’s mystical experience is over-determined byreligion and culture. This finding is also used to solve the other philosophical problemsthroughout the article. Consequently it is deduced that there are structural, proceduraland linguistic similarities rather than differences in the mystical experiences.